Paradoxical psoriasis: The flip side of idiopathic psoriasis or an autocephalous reversible drug reaction? - Jiawei Lu; Yan Lu (Journal of Translational Autoimmunity, 2023)
Psoriasis is a common, chronic skin disease that results mainly from the complex interplay between T cells, dendritic cells, and inflammatory cytokines including TNF-α, IL-17, IL-12, and IL-23. Successful therapy with anti-cytokine antibodies has proved the importance of these key cytokines, especially TNF-α. During the anti-TNF-α treatment of classical idiopathic psoriasis, a small portion of patients develop new psoriasiform lesions. This contradictory phenomenon was named paradoxical psoriasis which resembles idiopathic psoriasis clinically but presents overlapped histological patterns and distinct immunological processes. In this review, we discuss the differences between idiopathic psoriasis and paradoxical psoriasis with an emphasis on their innate immunity, as it is predominant in paradoxical psoriasis which exhibits type I IFN-mediated immunity without the activation of autoreactive T cells and memory T cells. We also put up an instructive algorithm for the management of paradoxical psoriasis. The decision on drug discontinuation or switching of biologics should be made based on the condition of underlying diseases and the severity of lesions.